2017
DOI: 10.18584/iipj.2017.8.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Miýo-pimātisiwin Developing Indigenous Cultural Responsiveness Theory (ICRT): Improving Indigenous Health and Well-Being

Abstract: The Truth and Reconciliation Commission of Canada calls upon those who can effect change within Canadian systems to recognize the value of Indigenous healing practices and to collaborate with Indigenous healers, Elders, and knowledge keepers where requested by Indigenous Peoples. This article presents the Indigenous Cultural Responsiveness Theory (ICRT) as a decolonized pathway designed to guide research that continuously improves the health, education, governance, and policies of Indigenous Peoples in Saskatc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 17 publications
0
51
0
Order By: Relevance
“…While it is important to teach graduate students, about protecting all things in creation, it is also necessary to ensure that there is an understanding that health institutions and systems have been created through a specific lens and way of being. In Canada (and in other countries around the world), colonization created a hierarchy of power and control that was replicated and perpetuated through institutions and structures like the health and education systems (45,46). Allan and Smylie (45) found that Indigenous people often face discrimination, racism and culturally unsafe spaces within the health care system.…”
Section: Traditional Knowledge and The Landmentioning
confidence: 99%
“…While it is important to teach graduate students, about protecting all things in creation, it is also necessary to ensure that there is an understanding that health institutions and systems have been created through a specific lens and way of being. In Canada (and in other countries around the world), colonization created a hierarchy of power and control that was replicated and perpetuated through institutions and structures like the health and education systems (45,46). Allan and Smylie (45) found that Indigenous people often face discrimination, racism and culturally unsafe spaces within the health care system.…”
Section: Traditional Knowledge and The Landmentioning
confidence: 99%
“…76 to land to health impacts such as religious practices, ceremonies, language fluency, ability to practice traditional activities and other measures of enculturation. 77,78 These frameworks have found positive associations between such activities and markers of health, such as lower rates of substance abuse, cardiovascular disease, and increased self-esteem and connection to community.…”
Section: Conceptual Framework Of Indigenous Culture and Healthmentioning
confidence: 99%
“…On the basis of qualitative interviews with indigenous patients with cancer, we recognized that indigenous patients often hold different world views from those of HCPs and the health-care system. 25 To understand how trust and perceptions of world view work with indigenous patients to impact SDM, our research question was as follows:…”
Section: Early Encounters Between Europeans and Indigenous Peoples Inmentioning
confidence: 99%
“…On the basis of qualitative interviews with indigenous patients with cancer, we recognized that indigenous patients often hold different world views from those of HCPs and the health‐care system . To understand how trust and perceptions of world view work with indigenous patients to impact SDM, our research question was as follows: “in a healthcare consultation involving Indigenous patients, for whom, why and in what situations do trust and perceptions of world view influence patient engagement to achieve SDM?”…”
Section: Introductionmentioning
confidence: 99%